Sensorineural hearing loss in very low birth weight infants with histological chorioamnionitis. (May 2015) - Vedovato, Stefania; Lo Iacono, Angela; Morando, Carla; Suppiej, Agnese; Orzan, Eva; Trevisanuto, Daniele; Visentin, Silvia; Cavallin, Francesco; Chiarelli, Silvia; Zanardo, Vincenzo
Abstract Objective: Histological chorioamnionitis (HCAM) has been associated with inflammatory diseases of preterm infants. Recently we have observed that it increased the risk of speech delay and hearing loss. So the aim of this study was to evaluate the relationship between sensorineural hearing loss (SNHL) of VLBW infants and HCAM. Methods: We performed an observational study on VLBW infants admitted to the NICU of Padua. Each patient with HCAM was matched with one control without HCAM. All infants underwent hearing screening before discharge by means of automated transient–evoked otoacustic emissions and automated auditory brainstem responses, which were repeated at 3 and 6 months of age with tympanometry measurement. Incidence of SNHL at 6 months of age was compared in the 2 groups and risk factors for hearing loss were studied. Results: Two of 77 (2.6%) newborns with HCAM e 6/73 (8.2%) without it presented SNHL at 6 months of corrected age (p = 0.16). Multivariable logistic regression analysis identified surgical ligation of patent ductus arteriosus (PDA) as independent predictors of SNHL (OR: 5.75, 95% CI 1.34–24.84, p = 0.02), whereas the effect of HCAM on SNHL was only near to statistical significance level. Conclusions: Surgical ligation of PDA is associated with an increased risk of SNHL in VLBW infants, regardless of HCAM.